Amorphous-to-crystalline transition and photoluminescence switching in guest-absorbing metal–organic network thin films. Issue 2 (5th December 2019) - Ghazy, Amr; Safdar, Muhammad; Lastusaari, Mika; Karppinen, Maarit
Abstract : Amorphous-to-crystalline (aMOF-to-MOF) transition and simultaneous quenching of luminescence are seen upon water absorption for Nd-terephthalate thin films grown using ALD/MLD method. Abstract : An amorphous metal–organic framework (aMOF) is an oxymoron as the porosity derived from the ordered network of the metal and organic moieties is the main characteristic of conventional crystalline MOFs. However, amorphous metal–organic materials can be synthesized from gaseous precursors through atomic/molecular layer deposition (ALD/MLD). We demonstrate an exciting interplay between luminescence properties and amorphous-to-crystalline transition realized upon water absorption in ALD/MLD aMOF films.